2021
DOI: 10.3390/pathogens10010081
|View full text |Cite
|
Sign up to set email alerts
|

The Role of a New Compound Micronutrient Multifunctional Fertilizer against Verticillium dahliae on Cotton

Abstract: Verticillium dahliae Kleb., the causal pathogen of vascular wilt, can seriously reduce the yield and quality of many crops, including cotton (Gossypium hirsutum). To control the harm caused by V. dahliae, considering the environmental pollution of chemical fungicides and their residues, the strategy of plant nutrition regulation is becoming increasingly important as an eco-friendly method for disease control. A new compound micronutrient fertilizer (CMF) found in our previous study could reduce the damage of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…Due to the stable dormant structure microsclerotia, long-term variability, and coevolution with host plants ( Ju et al, 2020 ; Höfer et al, 2021 ; Starke et al, 2021 ), controlling the spread of Verticillium wilt in plants remains challenging using currently available methods, such as chemical control, genetic breeding, and optimization of the cropping pattern ( Ostos et al, 2020 ; Ramirez-Gil and Morales-Osorio, 2021 ; Zhang Y. L. et al, 2021 ). Disease resistance breeding is limited by a long breeding cycle and a lack of natural resistance resources, and chemical control has no beneficial effect on the control of soil-borne diseases ( Diaz-Rueda et al, 2021 ; Hanika et al, 2021 ; Sunico et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the stable dormant structure microsclerotia, long-term variability, and coevolution with host plants ( Ju et al, 2020 ; Höfer et al, 2021 ; Starke et al, 2021 ), controlling the spread of Verticillium wilt in plants remains challenging using currently available methods, such as chemical control, genetic breeding, and optimization of the cropping pattern ( Ostos et al, 2020 ; Ramirez-Gil and Morales-Osorio, 2021 ; Zhang Y. L. et al, 2021 ). Disease resistance breeding is limited by a long breeding cycle and a lack of natural resistance resources, and chemical control has no beneficial effect on the control of soil-borne diseases ( Diaz-Rueda et al, 2021 ; Hanika et al, 2021 ; Sunico et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…P, Cu, Se, Zn, and other elements are essential nutrients for plants and livestock, and forage is a direct source of various nutrients for livestock. A lack or an excess of any elements may lead to unhealthy plants or prevent their growth and development, thus decreasing grassland biomass and forage nutritional quality, according to previous studies ( Saurabh et al, 2017 ; Yuan et al, 2016 ; Zhang et al, 2021 ). CP and DMD are important indicators with which to evaluate feed value and nutritional quality, which have direct impacts on livestock productivity and economic value ( Huo et al, 2006 ).…”
Section: Discussionmentioning
confidence: 86%
“…The use of fertilizer containing micronutrients, including zinc and manganese, has been proposed as an alternative to control Verticillium dahliae Kleb. [45]. These authors demonstrated by in vitro assay that these chemicals were responsible for mycelial growth inhibition, reduction of melanin production and microsclerosis of V. dahliae, in addition to associating this effect to the factor of certain micronutrients being also observed in inorganic fungicides.…”
Section: Physical-chemical Characteristics That Affect the Inhibiting Capacity Of Biocharsmentioning
confidence: 97%